Detección de antígenos de Dirofilaria immitis en caninos del Área Metropolitana del Valle de Aburrá (2006)
ABSTRACT: Our goal was to determine the presence or absence of the nematode Dirofilaria immitis in over-one-year old dogs of the Metropolitan area of the Aburra Valley. 300 dogs were tested with an inmunochromatography lateral flow kit. 285 samples fulfilled the inclusion and exclusion criteria, finding only one dog positive. It was concluded that this disease is not endemic in the studied area.